TINF2 Gene Mutation in a Patient with Pulmonary Fibrosis - T. W. Hoffman; J. J. van der Vis; M. F. M. van Oosterhout; H. W. van Es; D. A. van Kessel; J. C. Grutters; C. H. M. van Moorsel (Case Reports in Pulmonology)
Pulmonary fibrosis is a frequent manifestation of telomere syndromes. Telomere gene mutations are found in up to 25% and 3% of patients with familial disease and sporadic disease, respectively. The telomere gene TINF2 encodes an eponymous protein that is part of the shelterin complex, a complex involved in telomere protection and maintenance. A TINF2 gene mutation was recently reported in a family with pulmonary fibrosis. We identified a heterozygous Ser245Tyr mutation in the TINF2 gene of previously healthy female patient that presented with progressive cough due to pulmonary fibrosis as well as panhypogammaglobulinemia at age 52. Retrospective multidisciplinary evaluation classified her as a case of possible idiopathic pulmonary fibrosis. Telomere length-measurement indicated normal telomere length in the peripheral blood compartment. This is the first report of a TINF2 mutation in a patient with sporadic pulmonary fibrosis, which represents another association between TINF2 mutations and this disease. Furthermore, this case underlines the importance of telomere dysfunction and not telomere length alone in telomere syndromes and draws attention to hypogammaglobulinemia as a manifestation of telomere syndromes.